2011
DOI: 10.1029/2011jc007280
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between the decadal oscillations of the northern Ionian Sea and the salinity distributions in the eastern Mediterranean

Abstract: We study the impact of decadal inversions of the Ionian upper layer circulation (denominated as Adriatic‐Ionian Bimodal Oscillation System) on thermohaline properties of the Levantine and Cretan Seas. Lagrangian drifter data and surface geostrophic currents show that the Atlantic Water (AW) flow is well organized and most intense when the Ionian circulation is cyclonic. During the Ionian anticyclonic phase, the AW spreading pathway is the longest, contributing to its prolonged mixing and higher salinity once i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
116
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(134 citation statements)
references
References 26 publications
6
116
1
1
Order By: Relevance
“…Theocharis et al, [2002a] observed a few years after the EMT (1997-1999) a reversal of the upper layer circulation in the Central Ionian Sea which returned to the pre-EMT cyclonic pattern, while AW re-established its pre-EMT eastward flow toward the Levantine. Further studies [Borzelli et al, 2009;Gačić et al, 2010Gačić et al, , 2011Poulain et al, 2012] have confirmed that in both 1997 and 2006 the Ionian Sea upper circulation demonstrated reversals and concluded that the changes in the Ionian Sea upper layer circulation pattern is a recurrent phenomenon occurring on an almost decadal time scale. Gačić et al [2010Gačić et al [ , 2011 proposed a feedback mechanism, named the Adriatic-Ionian Bimodal Oscillating System (BiOS), between the observed North Ionian upper layer circulation inversions and the water mass redistributions in the Ionian Sea which relate to variations of the thermohaline properties of waters formed in the Southern Adriatic Sea.…”
Section: Deep Water In the Cretan Sea And The Eastern Mediterranean Tmentioning
confidence: 89%
See 2 more Smart Citations
“…Theocharis et al, [2002a] observed a few years after the EMT (1997-1999) a reversal of the upper layer circulation in the Central Ionian Sea which returned to the pre-EMT cyclonic pattern, while AW re-established its pre-EMT eastward flow toward the Levantine. Further studies [Borzelli et al, 2009;Gačić et al, 2010Gačić et al, , 2011Poulain et al, 2012] have confirmed that in both 1997 and 2006 the Ionian Sea upper circulation demonstrated reversals and concluded that the changes in the Ionian Sea upper layer circulation pattern is a recurrent phenomenon occurring on an almost decadal time scale. Gačić et al [2010Gačić et al [ , 2011 proposed a feedback mechanism, named the Adriatic-Ionian Bimodal Oscillating System (BiOS), between the observed North Ionian upper layer circulation inversions and the water mass redistributions in the Ionian Sea which relate to variations of the thermohaline properties of waters formed in the Southern Adriatic Sea.…”
Section: Deep Water In the Cretan Sea And The Eastern Mediterranean Tmentioning
confidence: 89%
“…These reversals are related to the spatial variability of the meandering AIS along with the respective reduction or restoration of the LIW/CIW flow in the North Ionian. The thermohaline pump mechanism proposed by Theocharis et al, [2014] differs from the BiOS mechanism proposed by Gačić et al [2010Gačić et al [ , 2011 Krokos et al [2014] showed that this pumping mechanism is an ongoing internal mechanism that led to the reactivation of the Aegean Sea during 2007-2009 almost a decade after the end of the EMT production period. Both Theocharis et al, [2014] and Krokos et al [2014] argue that the role of the internal mechanism seems to prevail over the long-term atmospheric influence in DWF events in the EMed.…”
Section: Deep Water In the Cretan Sea And The Eastern Mediterranean Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, there are some papers that consider the EMT to be a climate shift (e.g. Conversi et al, 2010), indicating uniqueness of the process; on the other hand, Gačić et al (2011) raise a possibility that the EMT may repeat when the preconditioning and severe wintertime cooling and winds coincide. High-resolution numerical modelling partially supports the latter: Beuvier et al (2010) applied the eddy-permitting numerical model for the 1960-2000 period and found that the EMT is dominantly driven by winds and surface fluxes over the Aegean, which were uniquely extreme during winters of 1991 and 1992, but which may repeat with longer return period than the investigated time interval in the future.…”
Section: Uniqueness Of the 1991-1998 Periodmentioning
confidence: 99%
“…These waters then flow towards the northwestern Ionian perimeter and, together with less dense MAW lying above them, stretch the water column and change geostrophic balance, resulting in a shift of the circulation to the cyclonic one. This important concept called Bimodal Adriatic-Ionian Oscillation (BiOS), which was introduced recently for the central Mediterranean Basin, was further extended towards the Levantine Basin and the EMT preconditioning (Gačić et al, 2011), and was found to explain a number of known phenomena such as decadal salinity oscillations in the Adriatic called the Adriatic ingressions (Buljan, 1953; and the decadal variation of the MAW meandering in the Ionian Sea (Malanotte-Rizzoli et al, 1997).…”
Section: Introductionmentioning
confidence: 99%